INVESTIGATION AND MODELING OF SYSTEMS WITH DISTRIBUTED PARAMETERS - A. P. Korneev; G. S. Lenevski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
A point of feedback switch eliminating resonances in closed electromechanical system along the whole length of a circle object without correcting devices has been determined. Methodology for obtaining a rational transfer function on the basis of resonance frequency distribution and object anti-resonances has been developed.